Generating Image From Brain Signals To Study Contemplate Human Mental Stability Using Artificial Intelligence - Prashita Rao, S.Saravana Kumar, Surbhi.k (International Journal of Advanced Science and Technology, 2020)
In recent years rapid progress has been made in neuroscience and artificial intelligence. The advancement of artificial intelligence leads to various applications. The brain is the most complex part of human and require thorough study of each part of brain that depicts a person’s thoughts, behavior and response. The thoughts and imagination occurring or happening in a person’s mind depicts the mental stability of the person, these thoughts and imaginations are converted into images with the help of artificial intelligence. A brain is an electrochemical organ, electrical activity emanating from the brain is displayed in the form of waves or brain waves .The human brain being a complex system is turning into attention catching term for developing technologies in the field of artificial intelligence. Electroencephalography (EEG) is an electrophysiological observation methodology to record electrical activity of brain. Clinically EEG refers to the recording of the brain’s spontaneous electrical activity over an amount of time, as recorded from multiple electrode placed on scalp. The data collected from subject is then converted into image by using deep neural network. We developed a deep learning framework that tend to learn a more compact and noise free representation of EEG data and employ it to come up with visual stimuli evoking specific brain responses and activities of an individual